Rural Access Index : A Key Development Indicator - Roberts, Peter; KC, Shyam; Rastogi, Cordula (World Bank, Washington, DC, 2014)
This paper describes the establishment of the Rural Access Index, one of several Transport Headline Indicators endorsed by the World Bank Transport Sector Board in 2003. The index has been adopted for the Results Measurement System (RMS)2 of the 14th round of the International Development Association (IDA-14) which was launched in July, 2005. The Index was developed in response to the consensus led by borrowers that it identifies an important priority for poverty reduction strategies in view of the established links between physical isolation and poverty. This provides stronger linkage to the Millennium Development Goals (MDG) and better assesses the contribution of IDA assistance to the sustainable development of the beneficiary countries. The Rural Access Index provides a consistent basis for estimating the proportion of the rural population which has adequate access to the transport system.